Persistent risk of HBV reactivation despite extensive lamivudine prophylaxis in haematopoietic stem cell transplant recipients who are anti-HBc-positive or HBV-negative recipients with an anti-HBc-positive donor. (November 2016) - Cerva, C.; Colagrossi, L.; Maffongelli, G.; Salpini, R.; Di Carlo, D.; Malagnino, V.; Battisti, A.; Ricciardi, A.; Pollicita, M.; Bianchi, A.; Picardi, A.; Cudillo, L.; et al.
Abstract: The overall rate of hepatitis B virus (HBV) reactivation was evaluated in a population of 373 haematological stem cell transplant (HSCT) patients treated with lamivudine (LMV) if they were anti-HBc-positive/HBV-DNA-negative recipients or if they were HBV-negative recipients with an anti-HBc-positive donor. The incidence of HBV reactivation was calculated in two groups of autologous (auto) or allogeneic (allo) HSCT patients who were stratified according to their HBV serostatus. The former group included 57 cases: 10 auto-HSCT and 27 allo-HSCT anti-HBc-positive recipients, two auto-HSCT and three allo-HSCT inactive carriers, and 15 allo-HSCT recipients with an anti-HBc-positive donor. Forty-seven (82.4%) patients in this group received LMV prophylaxis (the median (interquartile range, IQR) of LMV treatment was 30 (20–38) months). The second group consisted of 320 anti-HBc-negative auto-HSCT and allo-HSCT recipients with anti-HBc-negative donors. None of these patients received any prophylaxis. Two patients in the first group and two in the second group experienced reactivation of HBV infection, with an incidence of 3.5% (95% CI 0.4-12.1%) and 0.6% (95% CI 0.1-2.2%), respectively. Only one out of four reactivated patients was LMV-treated. The cumulative probability of HBV reactivation at 6 years from HSCT was 15.8% (95% CI 15.2-16.4%). Three of four viral isolates obtained from the HBV-reactivated patients harboured mutations in the immune-active HBsAg-region. In a HSCT population carefully evaluated for HBV prophylaxis, a risk of HBV reactivation persisted in the group of patients who were not LMV-treated. Only one LMV-treated patient experienced reactivation of HBV with a resistant HBV isolate.